Syphilis Seroprevalence and Its Correlates Among Blood Donors in The North-West Region of India - Jyotika, Jyotika; Saban, Prachi; Gupta, G. R.; Rachna, Rachna (Journal of Neonatal Surgery, 2025)
Background: Syphilis remains a globally important transfusion-transmissible infection (TTI). Although transfusion transmission is now rare due to routine donor screening, the detection of seropositive donations provides valuable information about community-level infection and blood safety. Objective: To determine the seroprevalence of syphilis and associated correlates among blood donors in the North-West region of India. Material & Methods: A cross-sectional study was conducted among 360 blood donors at a Manglam Diagnostic and Blood Center Hisar. Donor demographic and clinical data were collected using standardized forms. Blood samples were screened for Treponema pallidum antibodies using a treponemal enzyme-linked immunosorbent assay (ELISA), with reactive samples confirmed by the Venereal Disease Research Laboratory (VDRL) test. Results: Of the 360 donors tested, 5 (1.39%) were seropositive for syphilis. Seropositivity was higher among first-time donors (2.0%) compared to repeat donors (0.6%), and slightly higher among males (1.4%) than females (1.0%). Donors aged 31–40 years had the highest positivity rate (2.5%). Replacement donors had a higher prevalence (1.8%) than voluntary donors (0.9%). Conclusion: The seroprevalence of syphilis among blood donors in this North-West Indian cohort was low (1.39%) but non-negligible. Continued mandatory screening, donor education, and encouragement of voluntary repeat donations remain essential to maintain blood safety.